Inggris - Tahir, Takdir; Fatimah Farah Nur Suci Shabir (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Cancer is the second leading cause of death in the world after heart disease. Breast cancer (Carcinoma Mammae) is a malignant tumor (abnormal lump) that grows within the breast tissue. Most patients do not know exactly the cause of the cancer they suffer. Treatment of breast cancer often involves surgical procedures, such as biopsy excision including breast conservation surgery or mastectomy. The purpose of this case study is to find out the comparison of modified radical mastectomy (MRM) and biopsy excision procedures. The method used is descriptive analytical with a case study approach, which is a research method that aims to make a systematic and accurate description or description of the factual problem being studied. MRM and biopsy excision are both safe treatment options for early-stage mammary carcinoma. The determination of surgical action is seen from the spread of cancer and the stage using the classification of the TNM system. The results were obtained that there were differences in MRM and biopsy excision actions ranging from the type of anesthesia, the duration of the operation and the use of surgical wound drain. For this reason, the team of health workers determines the best choice for the patient's recovery. It is hoped that this case study will be used as a reference or information as well as a reference for future researchers and be useful for the progress of health workers.